2005
DOI: 10.1007/s11661-005-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical methods to detect susceptibility of Ni-Cr-Mo-W alloy 22 to intergranular corrosion

Abstract: Alloy 22 (UNS N06022), a Ni-Cr-Mo-W based alloy, is a candidate material for the outer wall of nuclear waste package (NWP) containers. Even though the alloy is highly stable at low temperatures, it could undergo microstructural changes during processing such as welding and stress relieving. Formation of topologically close-packed (TCP) phases such as , P, , etc. and Cr-rich carbides could make the material susceptible to localized corrosion. Hence, it is important to correlate the microstructural changes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…2,3). The obtained results are consistent with the general view that cold work before sensitization, reduces the intensity of intergranular corrosion [13][14][15]. This is due to the deformation of the structure (twins, slip bands, stacking errors, grain refinement) ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…2,3). The obtained results are consistent with the general view that cold work before sensitization, reduces the intensity of intergranular corrosion [13][14][15]. This is due to the deformation of the structure (twins, slip bands, stacking errors, grain refinement) ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…These alloys are widely used in a range of industrial applications, and Alloy 22 was recently considered as the corrosion barrier on packages for the permanent disposal of nuclear wastes . This last potential application stimulated many studies on this alloy and, to a lesser degree, other Ni‐Cr‐Mo alloys, on processes such as intergranular corrosion, localized corrosion with an emphasis on crevice corrosion, stress corrosion cracking, and general passive corrosion …”
Section: Introductionmentioning
confidence: 99%
“…[4] An extensive amount of research on Ni-Cr-Mo alloys has been reported. [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] One of the typical alloys is named Haynes 242 alloy with a nominal composition of Ni-8Cr-25Mo (wt.%); this material exhibits excellent high-temperature strength and ductility, low thermal expansion characteristics, good oxidation resistance and excellent fabricability. [1,2,5] The chemical composition and heat treatment of Ni-Cr-Mo alloys have also been investigated.…”
mentioning
confidence: 99%